(3GdELJgGO hGdJLOjO aj GdacQ GdGbJUGOj GdGSdGej GdeYGUQ (B:s (3OQGSI JMdjdjI fbOjI dCReGJ hOhQGJ GdacQ GdGbJUGOj GdQCSeGdj (B/s - (3GdchGOj, eMeOs ((3YeGf(B: s (3OGQ GdfaGFS(B, s, 2012)
(3GdOdGdGJ h GdQhGHW h GdCSS h GdVhGHW GdNGUI HGdGbJUGO eY GdJWQb Gdi edGeM h bVGjG GdacQ GdGbJUGOj GdGSdGej h CReGJ GdacQ GdGbJUGOj GdQCSeGdj h OhQjJgG Ydi VhA JLOjO h GLJgGOGJ GdacQ GdGbJUGOj GdGSdGej GdeYGUQs
((3GbJfjJ SfI (B2013 (3H(B09(3fSN(B) 2014(3H(B:03(3fSNs
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdGSdGejs; (3GdCfXeI GdGbJUGOjIs